Investigation of Optical Properties of Biological Tissues - Prokopyeva, E. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Optical methods of biological tissue investigation are the most promising in various applications such as biomedicine, agriculture, food control, due to their significant advantages. This paper describes the optical system for measuring optical parameters of back-scattered light, experiments were provided with pork chop slices.
Keywords: biological tissue; scattering; meat ageing; optical properties; polarization